Dangerous Science Science Policy and Risk Analysis for Scientists and Engineers - Rozell, Daniel J. (Ubiquity Press, 2020)
The public is generally enthusiastic about the latest science and technology, but sometimes research threatens the physical safety or ethical norms of society. When this happens, scientists and engineers can find themselves unprepared in the midst of an intense science policy debate. In the absence of convincing evidence, technological optimists and skeptics struggle to build consensus. In these situations, it is best to sidestep the instigating controversy by using a broad risk-benefit assessment as a risk exploration tool to help scientists and engineers accomplish their goals while avoiding physical or moral dangers. Dangerous Science explores the intersection of science policy and risk analysis to determine ways to minimize negative impacts of science and technology on society.